Kinetics of overarm throwing motion for skilled Japanese elementary school boys - Kobayashi, Y.; Ae, M.; Miyazaki, A.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the kinetics of overarm throwing for skilled Japanese elementary school boys, in order to gain insight into children`s throwing motion. The throwing motions of 42 boys from the second, fourth, and sixth grade were videotaped using three high-speed cameras; and seven boys from each grade were selected for 3D motion analysis, based on their throwing distance. Although no difference in the elbow extension torque before the release was observed, the angular velocity and the joint torque of the shoulder external/internal rotation tended to be greater for students of higher grades. Thus, the sixth graders tended to depend more on shoulder external/internal rotation with the effective use of a stretch-shortening cycle of the shoulder muscles, while the second graders seemed to depend more on elbow extension.